Effect of ultrasonic treatment on the water hydration capacity, viscocity, and granule size of cassava starch. - Historiador, Martina Gamboa (2017.)
Starch is the principal energy reserve found in plants and tubers and is used to control the consistency and texture of foods. The limits to the use of native starch is its weak structure which can be modified through chemical, enzymatic, or physical means. This study explored the effect of ultrasonic treatment on the physical properties of cassava starch using a Completely Ramdomized Design (CRD). The water hydration capacity, viscosity, and granule size of native and modified cassava starch were compared with the non-treated sample (native starch) using a Mann Whitney U Test at 95% confidence interval. The water hydration increased from 2.1347 g/g to 2.357 g/g. The granule size decreased by about 2 microns and, in turn, significantly reduced the viscosity from 184.44 centipoise. Sensory evaluation showed that gravy produced using native starch was found to have a thicker consistency and lighter color whereas the gravy made with modified starch had a runnier consistency and darker color. A paired preference test was conducted to determine the more preferred gravy, which was the gravy made with modified starch. The general acceptability of the preferred gravy was rated as ?likely very much?. The results show that ultrasonic treatment was effective enough to produce significant changes in the physical properties of cassava starch and, therefore, has potential to be used in the food industry.
Thesis - B.S. (Food Technology) - School of Technology, University of the Philippines Visayas.
Keywords: Cassava; Starch; Ultrasonic treatment